2018
DOI: 10.1177/0009922818778042
|View full text |Cite
|
Sign up to set email alerts
|

Adequate or Inadequate? The Volume of Blood Submitted for Blood Culture at a Tertiary Children’s Hospital

Abstract: The volume of blood sampled for culture critically influences the results. This study aimed to determine (1) the volume of blood submitted for culture, (2) the proportion of blood cultures with adequate volume, (3) whether measured improvement from a previous educational intervention had been sustained, and (4) the impact of blood volume on culture result. The volume of blood submitted for cultures was determined over a 13-month period by weighing bottles before and after collection and before and after an edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Definitely, it is recommended to collect a weight-or age-dependent blood volume and inoculate this sample into one paediatric or adult aerobic BC bottle if the total volume sampled does not exceed 4e5 mL or 10 mL, respectively [27e29, 39,45]. For quality management reasons it is strongly recommended that monitoring be performed frequently and that all personnel involved in drawing blood be trained regarding sampling volume and processing [39,40,43]. Besides BC, molecular-based diagnostics may be an interesting alternative in future, with the advantage of requiring a small blood volume.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Definitely, it is recommended to collect a weight-or age-dependent blood volume and inoculate this sample into one paediatric or adult aerobic BC bottle if the total volume sampled does not exceed 4e5 mL or 10 mL, respectively [27e29, 39,45]. For quality management reasons it is strongly recommended that monitoring be performed frequently and that all personnel involved in drawing blood be trained regarding sampling volume and processing [39,40,43]. Besides BC, molecular-based diagnostics may be an interesting alternative in future, with the advantage of requiring a small blood volume.…”
Section: Discussionmentioning
confidence: 99%
“…Despite proper aseptic handling, the BC contamination rate is 1e3%, resulting in inconclusive diagnosis, unnecessary antimicrobial treatment [1], increased mortality of patients with suspected sepsis, and a burden on the health system [39]. In addition to aseptic BC procedure and methodology, inadequate blood volume inoculation into culture bottles is associated with a disproportionate risk of culturing contaminants [43]. A recent study conducted at Batson Children's Hospital in Jackson, Mississippi (USA), demonstrated a decrease in contamination rates from 2.85% to 1.54% as a result of introducing a standardized blood sampling method with optimized (weight-based) volume (Table 1) and personnel training [39].…”
Section: Blood Volume and Contaminationmentioning
confidence: 99%
“…Many articles however recommend an age-based sampling strategy illustrated in Table 5 (166, 170, 171). This age-based sampling is convenient and safe, as the volumes are noticeably smaller than with weight-based guidelines (see Figure 7 for an example in LMICs).…”
Section: Methods and Techniques For Processing Manual Blood Culturesmentioning
confidence: 99%
“…Different biomarkers are currently used for the diagnosis of neonatal sepsis, such as white blood count and absolute neutrophil count, procalcitonin, C-reactive protein, and cytokines, but they have a very low positive predictive value due to the low specificity [5][6][7][8][9]. Blood culture is considered the gold standard for the diagnosis of neonatal sepsis, but its positivity rate is affected by volume of blood submitted for culture, level of bacteremia, or prenatal antibiotic use, which can delay the growth of bacteria and the time to positivity with a negative impact on the sensitivity of the test [10,11].…”
Section: Introductionmentioning
confidence: 99%